Nutritional value and antioxidant properties of Cannabis seeds from Makwanpur district of central Nepal - Dawadi, Prabin; Syangtan, Gopiram; Siddiqui, Mohammad Ataullah; Lama, Bhupendra; Nepal, Kaushal; Joshi, Dev Raj; Bhatt, Lok Ranjan (Scientific World, 2022)
Cannabis seeds have been recognized as one of the most nutritionally complete food sources which are also used for medicinal as well as recreational purposes. In the present study, nutritional, phytochemical, antioxidant and antimicrobial properties of seeds of Cannabis sativa and Cannabis indica, collected from Makawanpur district, central Nepal were evaluated. Nutritional and phytochemical analysis was mainly based on the Association of Official Analytical Chemists (AOAC) methods, while antibacterial activity was tested using the agar well diffusion method. The results revealed that Cannabis seeds contain considerable amount of protein (32.08% to 43.04%), fat (30.86% to 42.40%), carbohydrate (8.39% to 13.79%), total phenolics (701.05 mg/100g to 1312.72 mg/100g), and total flavonoids (366.29 mg/100g to 385.12 mg/100g). The radical scavenging activity of the seeds ranges from 37.83% to 54.84% at the concentration of 6.25 µg/mL. The results indicate that both the species hold high and substantial antioxidant activities.